Multimedia dan islam - ABU Bakar Abdul Majeed; SITI Fatimah Abdul Rahman; Siti Fatimah Abdul Rahman; Abu Bakar Abdul Majeed; Institut Kefahaman Islam, Malaysia (K.Lumpur: Institut Kefahaman Islam Malaysias, 2000)
On Malaysian Muslim community and issues on multimedia computing; collection of articles.
Includes bibliographical references and index.
Keywords: Multimedia systems in management; Islam and science; Multimedia systems - Religious aspects - Islam; Multimedia systems -- -- Indonesia; Computers -- -- Religious aspects -- -- Islam; Multimedia systems